Exploring the Addition of Mango Peel in Functional Semolina Sourdough Bread Production for Sustainable Bio-Reuse - María Eugenia Chulibert; Pasquale Roppolo; Carla Buzzanca; Antonio Alfonzo; Enrico Viola; Lino Sciurba; Ilenia Tinebra; Angela D'Amico; Vittorio Farina; Daniela Piazzese; Vita Di Stefano; Marcella Barbera; et al. (MDPI AG, 2024)
Mango, a tropical fruit celebrated for its delightful fragrance and high nutritional value, generates significant waste during processing, with approximately 35-60% of the fruit being discarded. However, this waste contains valuable components, such as fibre, carotenoids, polyphenols, and other bioactive compounds. In an effort to repurpose mango peel, this study dehydrated it to create mango peel powder (MPP), which was then incorporated into sourdough bread to produce functional breads with enhanced nutritional value. Semolina was replaced with MPP at levels of 5% (MPP-5) and 10% (MPP-10) (w/w). After dehydration, the mango peel had a yield of 22%, and the procedure used did not cause any organoleptic changes. The bread fermentation process was conducted at 30 °C for 8 h. During dough fermentation, the pH was monitored, showing a value of 4.14 ± 0.02 in the MPP-10 dough. Overall, the MPP-10 bread received a higher score (6.51) than the control (CTR) bread (5.6) and the MPP-5 bread (6.11). The total phenolic content of the fortified breads ranged from 44.760 to 98.931 mg gallic acid equivalents (GAE)/g, and the antiradical activity ranged from 15.213 to 29.461 mmol trolox equivalent antioxidant activity (TEAC)/100 g, depending on the percentage of enrichment.